Software Product Line Engineering Foundations, Principles and Techniques - Pohl, Klaus; Böckle, Günter; van der Linden, Frank J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
I. Software Product Line Engineering Are you interested in producing software products or software-intensive systems at lower costs, in shorter time, and with higher quality? If so, you are holding the right book in your hands. Software product line engineering has proven to be the methodology for Higher quality, lower developing a diversity of software products and software-intensive systems cost, and shorter at lower costs, in shorter time, and with higher quality. Numerous reports development times document the significant achievements and experience gained by introducing software product lines in the software industry. Chapter 21 of this book summarises several cases. Concerning the terminology, there is an almost synonymous use of the terms Software product line “software product family” and “software product line”. Whereas in Europe vs. software product the term software product family is used more often, in North America the family term software product line is used more frequently. This is, among other things, reflected in the names of the two former conference series (the so- ware product line conference series, started in 2000 in the USA, and the product family engineering (PFE) workshop series, started in 1996 in Europe) which were merged in 2004 to form the leading software product line conference (SPLC) series. In this book, we use the term software product line.
to Software Product Line Engineering -- A Framework for Software Product Line Engineering -- Overview of the Example Domain: Home Automation -- Product Line Variability -- Principles of Variability -- Documenting Variability in Requirements Artefacts -- Documenting Variability in Design Artefacts -- Documenting Variability in Realisation Artefacts -- Documenting Variability in Test Artefacts -- Domain Engineering -- Product Management -- Domain Requirements Engineering -- Domain Design -- Domain Realisation -- Domain Testing -- Selecting High-Level COTS Components -- Application Engineering -- Application Requirements Engineering -- Application Design -- Application Realisation -- Application Testing -- Organisation Aspects -- Organisation -- Transition Process -- Experience and Future Research -- Experiences with Software Product Line Engineering -- Future Research.
Keywords: Computers; Software engineering; Management information systems; Computer science; Information technology; Business—Data processing; Management; Industrial management; Theory of Computation; Software Engineering/Programming and Operating Systems; Software Engineering; Management of Computing and Information Systems; IT in Business; Innovation/Technology Management